Analisis Organisasi & Pengembangan Kapasitas Kelembagaan Pada Sektor Wisata: (Studi di Dinas Pariwisata, Kebudayaan, Pemuda & Olahraga Kabupaten Pekalongan) - Tri Lestari Hadiati; Riyadi Riyadi (Universitas 17 Agustus 1945 Semarang, 2023)
The problems that exist in the Pekalongan Regency Tourism, Culture, Youth and Sports Office (Disporapar) on the one hand are problems in the organisational structure, especially in charge of Tourism, which has no sub-fields, even though the workload is very high. Another problem is that many tasks in the tourism sector have not been handled properly, such as the implementation of the licensing process and public services in the tourism sector, the implementation of qualifications and administration of tourism services, coordination and formulation of standards, norms and tourism promotion, and facilitation of tourism product development and the tourism business world and the creative economy in the tourism sector. On the other hand, it is a heavy responsibility for Disporapar to coordinate, communicate and socialise due to the low participation of the community to become